ANALISIS STRATEGI ALIANSI PADA PROGRAM KEMITRAAN LOCAL BUSINESS DEVELOPMENT TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA LBD PT. CHEVRON PACIFIC INDONESIA, DAERAH OPERASI SUMATERA) - Armizal, Armizal; Taufiqurrahman, Taufiqurrahman (Jurnal Ekonomi, 2014)
This research was held at PT Chevron Pacific Indonesia (CPI) Sumatera operations in Pekanbaru, consisting 9 district operations covered regional of Rumbai, Minas, Petapahan, Bekasap, Kopar, Pinggir, Bangko/Tanah Putih/Rohil, Duri dan Dumai. The purpose of this research is to analyze factors which influence partnership quality to the benefit of company performance through long time commitment, communications, risk sharing, flexibility, and corporate culture.Research was done by using closed-questionnaire method on 105 respondents. Respondents of this research are the company directors or authorized power of directors. Based on the research done using Structural Equation Method with AMOS 18 software on the full model of research, we come up with the conclusions that the result fulfilled most of goodness of fit criteria among others: Chi-square = 1207,361; Probabilitas = 0,000; RMSEA = 0,231; CFI = 0,974; AGFI = 0,931; CMIN/DF = 6,256; TLI = 0,942; DAN CFI = 0,956. It concludes that the model is fit to be used. These results describe that long time commitment, communications, risk sharing, flexibility are influencing quality of partnerships and take effect to corporate performance. However, commitment and corporate culture are not significantly influencing quality of partnerships.